Draft Annual Plan 1993-94 Part-I: Summary of Sectoral Outlay and Statistical Statements Union Territory of Daman and Diu - Planning Commission (Planning Commission, 1993)
Both Daman & Diu have four seasons. These being summer season from March to May, South west monsoon from June to September, post monsoon from October to November and winter season from December to February. Despite humidity the climate is pleasant.
Union Territory of Daman and Diu, Department of Planning and Statistics